Evaluación del comportamiento agronómico de cuatro variedades de pastosen la zona del cantón Puebloviejo - Bonilla Barros, Carlos Augusto (2016)
SUMMARY This research was conducted on the grounds of the Hcda. "Envidia" owned by Mr. Felipe Barros Portilla, located 3 km from the Puebloviejo way - Windows between the geographical coordinates of 79 ° 32 'west longitude and 01 ° 32' south latitude, with a height of 32 meters. The area is humid tropical climate, with an average temperature of 25.7 ° C and an average annual rainfall of 1925 mm. Marandu (Brachiariabrizanthacv), seeds of Toledo (. Brachiariabrizanthacv) was used as pasture genetic material; Mombasa (Panicum maximum cv.) And planting grass Savoie (Panicum maximum cv.). For the implementation of results experimental design "Randomized Complete Blocks" with four treatments and five repetitions was used, whose averages were subjected to the test Tukey. For crop development were carried out the following tasks, such as: analysis and soil preparation, planting, watering, weeding, fertilizing and harvesting. Germination percentage, days to flowering, leaf length and width, plant height, green and dry weight per hectare and economic analysis subject: to evaluate the agronomic performance of varieties, the following data were taken. According to the results it was concluded that the grass Toledo (Brachiariabrizanthacv.) And Mombasa (Panicum maximum cv.) Achieved a favorable agronomic performance in the area of Puebloviejo; the greater plant height, length and width of the sheets obtained Mombasa grass; in the variable days to flowering, grass flourished Mombasa late compared to other varieties and the greater weight of dry and green matter / ha was reported by the grass Toledo, with 14,762.0 and 6,832.0 kg / ha, respectively.